Multiple Giant Tarlov Cysts Presenting as Polyradiculopathy: A Rare Manifestation - Ahmed, K; Rauniyar, RK; Sah, PL; Dhungel, K; Gupta, MK; Ansari, S (Nepalese Journal of Radiology, 2012)
We describe a case of multiple giant Tarlov cysts presenting with complaints of low back pain with neurological claudication. Tarlov cysts are nerve root cysts found most commonly in the sacral roots, arising between the covering layer of the perineurium and the endoneurium near the dorsal root ganglion. Most of them are asymptomatic, usually detected as incidental findings on MRI. Symptomatic Tarlov cysts are extremely rare, commonly presenting as sacral or lumbar pain syndromes, sciatica or rarely as cauda equina syndrome. Tarlov cysts should be considered in the differential diagnosis of patients presenting with these complaints. NJR I VOL 2 I ISSUE 1 57-60 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6984